Inactive Archives Management at PT Pelabuhan Indonesia (Persero) - Melisa, Melisa; Darwis, Muh; Isgunandar, Isgunandar (ASHA Publishing, 2025)
This study aims to determine the management of inactive archives in PT Pelabuhan Indonesia (Persero) Regional 4. The approach used is qualitative with a descriptive type of research. Data collection techniques include observation, interviews, and documentation, which are then analyzed through the stages of data collection, data condensation, data presentation, and conclusion drawn. The results of the study show that the management of inactive archives is optimal. The process of transferring archives is carried out in accordance with the 2022 Archive Transfer Procedure, including the identification of archives, the preparation of transfer minutes by the person in charge, and the transfer of archives from the processing unit to the person in charge of archives. Archival arrangement and storage are carried out by reconstruction, data processing, and physical archives, arrangement in boxes, and creation of inactive archive lists. The archive service uses the P-ERCENT (Pelindo Electronic Record Center) application, although it is not yet fully operational. The process of destroying archives refers to the 2022 Archive Depreciation Procedure, including the formation of an assessment team, identification and selection of archives, submission of a list of archives for destruction, as well as assessment and approval from ANRI for archives with a retention of 10 years and more. The destruction was carried out by the cooperative vendor and reported by the person in charge of the archives.